Comparative Analysis of the Core Proteomes among the Pseudomonas Major Evolutionary Groups Reveals Species-Specific Adaptations for Pseudomonas aeruginosa and Pseudomonas chlororaphis - Marios Nikolaidis (Diversity, 2020)
The Pseudomonas genus includes many species living in diverse environments and hosts. It is important to understand which are the major evolutionary groups and what are the genomic/proteomic components they have in common or are unique. Towards this goal, we analyzed 494 complete Pseudomonas proteomes and identified 297 core-orthologues. The subsequent phylogenomic analysis revealed two well-defined species (Pseudomonas aeruginosa and Pseudomonas chlororaphis) and four wider phylogenetic groups (Pseudomonas fluorescens, Pseudomonas stutzeri, Pseudomonas syringae, Pseudomonas putida) with a sufficient number of proteomes. As expected, the genus-level core proteome was highly enriched for proteins involved in metabolism, translation, and transcription. In addition, between 39–70% of the core proteins in each group had a significant presence in each of all the other groups. Group-specific core proteins were also identified, with P. aeruginosa having the highest number of these and P. fluorescens having none. We identified several P. aeruginosa-specific core proteins (such as CntL, CntM, PlcB, Acp1, MucE, SrfA, Tse1, Tsi2, Tse3, and EsrC) that are known to play an important role in its pathogenicity. Finally, a holin family bacteriocin and a mitomycin-like biosynthetic protein were found to be core-specific for P. cholororaphis and we hypothesize that these proteins may confer a competitive advantage against other root-colonizers.